THE MEDIATING ROLE OF BRAND IMAGE IN THE EFFECT OF PRICE FAIRNESS ON CONSUMER PURCHASE DECISION(A Study on NVN Urban Café Consumers) - Putu Agung Novan Surya Saputra; Tjokorda Gde Raka Sukawati (Adisam Publisher, 2025)
The food and beverage industry is currently one of the most promising sectors in Indonesia. Many entrepreneurs are interested in venturing into this field, often realized through the establishment of various coffee shops. One such establishment in Denpasar City is NVN Urban Café. This study aims to analyze the effect of price fairness on purchase decisions, mediated by brand image. The sample consists of 100 respondents who are visitors of NVN Urban Café. The sampling technique employed is purposive sampling. This study utilizes path analysis, the Sobel test, and the Variance Accounted For (VAF) test. The results indicate that price fairness has a positive and significant effect on purchase decisions; price fairness also has a positive and significant effect on brand image; brand image positively and significantly affects purchase decisions; and brand image mediates the relationship between price fairness and purchase decisions.